2021
DOI: 10.3390/nu13030870
|View full text |Cite
|
Sign up to set email alerts
|

In the Age of Viral Pandemic, Can Ingredients Inspired by Human Milk and Infant Nutrition Be Repurposed to Support the Immune System?

Abstract: In 2020, with the advent of a pandemic touching all aspects of global life, there is a renewed interest in nutrition solutions to support the immune system. Infants are vulnerable to infection and breastfeeding has been demonstrated to provide protection. As such, human milk is a great model for sources of functional nutrition ingredients, which may play direct roles in protection against viral diseases. This review aims to summarize the literature around human milk (lactoferrin, milk fat globule membrane, ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 261 publications
(153 reference statements)
0
17
0
1
Order By: Relevance
“…Host innate-immune directed antiviral strategies offer the potential to work against multiple respiratory pathogens. Such therapeutics include antimicrobial molecules which can directly act as effectors against the virus, such as cathelicidins, lactoferrin, or vitamin D [85][86][87][88]. Recently, a defensin-like peptide (P9R) was reported to be effective against many pH-dependent viruses including RV, coronavirus (SARS-CoV, SARS-CoV-2, and MERS-CoV), and influenza viruses (H1N1, H7N9) [89].…”
Section: Rv Treatment Strategiesmentioning
confidence: 99%
“…Host innate-immune directed antiviral strategies offer the potential to work against multiple respiratory pathogens. Such therapeutics include antimicrobial molecules which can directly act as effectors against the virus, such as cathelicidins, lactoferrin, or vitamin D [85][86][87][88]. Recently, a defensin-like peptide (P9R) was reported to be effective against many pH-dependent viruses including RV, coronavirus (SARS-CoV, SARS-CoV-2, and MERS-CoV), and influenza viruses (H1N1, H7N9) [89].…”
Section: Rv Treatment Strategiesmentioning
confidence: 99%
“…It contributes to the development of the newborn’s immune system and contains several substances with a marked antiviral activity [17]. For some of these substances (Table 1), such as lactoferrin and human milk oligosaccharides, the antiviral activity has been attributed such a great importance that they have been supplemented to support immunity and provide antiviral protection of adult individuals [18, 19].…”
Section: Support Of Breastfeeding During the Covid-19 Pandemicmentioning
confidence: 99%
“…Traditional methods of producing infant formulas have discarded the bovine milk fat in favor of vegetable oils ( 28 ). However, in vitro , preclinical, and clinical studies have demonstrated numerous potential health benefits of MFGM ( 9 , 10 ). A systematic review and meta-analysis of MFGM supplementation in infants and children supported beneficial effects of MFGM on cognitive development and on reduction in otitis media incidence ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, specific human milk components may confer protection against infection by acting as decoy receptors to block the attachment of pathogens to host cell surfaces, including anti-RV secretory immunoglobulin A (sIgA) ( 6 ) and human milk oligosaccharides ( 7 , 8 ). Over the past two decades, both in vivo and in vitro studies have demonstrated health benefits associated with Milk Fat Globule Membrane (MFGM) and its component proteins, carbohydrates, and fats ( 9 , 10 ), including improved neurocognitive development, metabolism ( 11 ) and reduced infectious disease ( 12 , 13 ). In addition, both the lipid and protein fractions of MFGM reduce RV infectivity in vitro ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation